2001
DOI: 10.1080/00140130117282
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of working environmental conditions in VDT work

Abstract: The combined effects of city noise and luminance of the computer display were evaluated from the changes in lymphocytes and mental activities of participants. Healthy male students were tested under the following four experimental conditions: (1) a calculating task on a video display terminal (VDT) with luminance of 90 cd m(-2) without city noise; (2) a calculating task on a VDT with luminance of 20 cd m(-2) without city noise; (3) a calculating task on a VDT with luminance of 90 cd m(-2) with city noise of 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The mean HR is approximately 76 beats per minute (bpm) during the first half hour of the browsing task, and it monotonically decreases with browsing time. This decreasing trend agrees with the findings of previous VDT studies (Higuchi et al, 2003;Takahashi et al, 2001). The mean HR reaches a minimum of 68 bpm at 4 to 4.5 hours.…”
Section: Hrsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean HR is approximately 76 beats per minute (bpm) during the first half hour of the browsing task, and it monotonically decreases with browsing time. This decreasing trend agrees with the findings of previous VDT studies (Higuchi et al, 2003;Takahashi et al, 2001). The mean HR reaches a minimum of 68 bpm at 4 to 4.5 hours.…”
Section: Hrsupporting
confidence: 92%
“…Uncomfortable symptoms arising from video display terminal (VDT) tasks may include visual fatigue (Bergqvist & Knave, 1994;Sheedy, 1992) and musculoskeletal complaints (Li & Buckle, 1999), and much research on VDT tasks has been reported. Questionnaires have been widely used to investigate psychological fatigue during VDT tasks (Dillon & Emurian, 1995;Dillon, Kleinman, Choi, & Bias, 2005;Duffy & Chan, 2002;Stüdeli & Menozzi, 2003), whereas other studies have gathered physiological signals by electroencephalography (Shieh, Chen, & Wang, 2005), electromyography (Balci & Aghazadeh, 2004;Murata, Uetake, Matsumoto, & Takasawa, 2003;Park, Kim, & Shin, 2000;Seghers, Jochen, & Spaepen, 2003), and critical flicker fusion (Chi & Lin, 1998;Takahashi et al, 2001) to measure physiological fatigue. Heart rate (HR) has been measured in VDT tasks at low load levels (Higuchi, Motohashi, Liu, Ahara, & Kaneko, 2003;Takahashi et al, 2001); however, the change in HR is not remarkable when it is compared with the high loading task like HR recovery after exhausted exercise (Du et al, 2005;Platisa, Mazic, Nestorovic, & Gal, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies regard this type of workers. The possible sources of stress and mental fatigue for these workers are identified in workplace features, such as microclimate, noise and ergonomic factors (11), organizational factors such as repetitiveness, monotony of tasks, dissatisfaction, excessive sedentariness, prolonged time in using YOU and low possibility of human relations (8)(9)(10)(11)(12)(13). For these factors, a correlation with an increase in aesthenopia and musculoskeletal symptoms is also demonstrated (9-10, 12-13).…”
Section: Discussionmentioning
confidence: 99%
“…The critical flicker fusion frequency (CFF) test is a suitable method for the measurement of short-term visual strain 5,6) , however, few studies have indicated that CFF is sensitive as an objective measure of chronic fatigue. Therefore other convenient tools are required to detect exhausted workers at risk.…”
mentioning
confidence: 99%